The Influence of Organizational Behavior and Leadership on Employee Performance with Job Satisfaction as an Intervening Variable at the Sidikalang Sub-district Office, Dairi Regency - Isran Bintang; Kiki Farida Ferine; Abdi Sugiarto (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of Leadership and Organizational Behavior on Employee Performance with Job Satisfaction as an intervening variable in the Sidikalang District Office, Dairi Regency. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). Data was collected through the distribution of questionnaires to employees, then analyzed using SmartPLS software version 3.0. The results of the direct influence analysis showed that Leadership (X2) had a positive and significant effect on Employee Performance (Y) with a path coefficient of 1.060, a T-Statistics value of 19.053 (> 1.96), and P-Values = 0.000. Meanwhile, Organizational Behavior (X1) had no significant effect on Employee Performance, with a path coefficient of 0.134, a T-Statistics value of 1.596 (< 1.96), and P-Values = 0.117. In addition, Leadership also has a positive and significant effect on Job Satisfaction (Z) with a path coefficient of 1.060, a T-Statistics value of 19.053, and P-Values = 0.000, while Organizational Behavior has no significant effect on Job Satisfaction, with a path coefficient of -0.110, a T-Statistics value of 1.585, and P-Values = 0.120. Furthermore, the results of the study show that Job Satisfaction has a positive and significant effect on Employee Performance, with a path coefficient of 1.118, a T-Statistics value of 4.911, and P-Values = 0.000. The results of the indirect influence analysis (mediation) showed that Job Satisfaction was able to significantly mediate the relationship between Leadership and Employee Performance, with a path coefficient of 1.185, a T-Statistics value of 4.340, and P-Values = 0.000. However, Job Satisfaction was not able to mediate the influence of Organizational Behavior on Employee Performance, with a path coefficient of -0.123, a T-Statistics value of 1.341, and P-Values = 0.186. Based on these findings, it is suggested that the Sidikalang District Office focus more attention on improving the quality of leadership and employee job satisfaction as an effort to improve employee performance. Improvements in the aspect of Organizational Behavior alone are not enough to have a significant impact on improving employee performance.